2016
DOI: 10.1111/vru.12438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Image Plane, Patient Positioning, and Foraminal Zone on Magnetic Resonance Imaging Measurements of Canine Lumbosacral Intervertebral Foramina

Abstract: Degenerative lumbosacral stenosis has been suspected to have a dynamic component, especially regarding encroachment of the L7 nerve roots exiting the lumbosacral foramina. Angled cross-sectional imaging of the neuroforamina has been found improve the accuracy of the diagnosis of stenosis in humans. In this anatomic study, foraminal apertures were evaluated by MRI at the entry, middle, and exit zones of the nerve roots in 30 dogs that were clinically affected by lumbosacral disease. Standard vs. oblique planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
(83 reference statements)
2
18
0
Order By: Relevance
“…Similar findings have been reported for radiographic measures of lumbosacral range of motion in dogs . In the present study, mean lumbosacral angles were greater in flexion than extension for both measurement techniques, a phenomenon previously documented with CT and MRI …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar findings have been reported for radiographic measures of lumbosacral range of motion in dogs . In the present study, mean lumbosacral angles were greater in flexion than extension for both measurement techniques, a phenomenon previously documented with CT and MRI …”
Section: Discussionsupporting
confidence: 91%
“…In the present study, significant differences in intervertebral foraminal area were found between parasagittal and parasagittal oblique planar measurement methods. Previous studies also found differences between parasagittal and parasagittal oblique methods for quantifying intervertebral foraminal areas at L7‐S1 using CT and MRI . In both of these studies, the parasagittal planar method for measuring intervertebral foraminal area yielded values that were significantly larger than the parasagittal oblique measurement techniques.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Dynamic imaging techniques, in which the patient is imaged with the spine in a flexed and extended position, have been shown to detect changes that may be underestimated or missed on neutral imaging in the canine cervical spine 6 . Recent veterinary studies have shown that dynamic positioning leads to a change in LS foramina, which may be clinically significant 5,7‐9 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown low rates of interobserver agreement on some measurements performed in the LS spine 10,11 . Many studies that have evaluated measurements of the LS spine to differentiate between affected and unaffected dogs have had only one observer performing the measurements 5,7‐9 . The anatomy of the LS spine is complex especially around the foramina, making it especially important to confirm interobserver agreement when attempting to create a clinically useful reference range.…”
Section: Introductionmentioning
confidence: 99%